Dialética e retórica no discurso de Betti Katzenstein - Borsato, Cláudia Roberta; Cunha, Marcus Vinicius da (Revista Educação e Cultura Contemporânea, 2011)
Este trabalho examina uma série de artigos de autoria de Betti Katzenstein publicada na coluna Clínica Psicológica, seção do Caderno Feminino do jornal Folha da Manhã, entre 1947 e 1948. A análise emprega os recursos teórico-metodológicos adotados pelo Grupo de Pesquisa Retórica e Argumentação na Pedagogia (USP/CNPq), cujos fundamentos encontram-se na obra de Chaí¯m Perelman e de outros autores vinculados ao movimento de revisão da filosofia de Aristóteles iniciado na primeira metade do século XX. Nessa metodologia, consideram-se os três elementos centrais da retórica, segundo Aristóteles: as qualificações do orador, as disposições do auditório e o discurso proferido. O trabalho apresenta informações biográficas sobre Katzenstein, no intuito de posicioná-la como oradora autorizada a discorrer sobre temáticas psicológicas e educacionais. Apresenta também uma descrição do contexto em que a oradora se pronuncia, focalizando particularmente o movimento educacional renovador denominado Escola Nova. Com base nesses dados, é feita a caracterização dos auditórios a que se dirigem os artigos, os quais são examinados segundo os conceitos de dialética e retórica. Palavras chaves: Educação Brasileira - Escola Nova - Discurso Pedagógico - Análise Retórica Dialectic and rhetoric in the discourse of Betti Katzenstein Abstract This work examines a series of articles written by Betti Katzenstein and published between 1947 and 1948 in the column Psychological Clinical, a feminine section of a São Paulo journal of news named Folha da Manhã. The analysis uses the theoretical-methodological resources adopted by the Rhetoric and Argumentation in Pedagogy Research Group (USP/CNPq), which foundations are in Chaí¯m Perelman’s work and other authors linked to the revision of Aristotle"s philosophy started in the first half of 20th century. In that methodology, three central elements of the rhetoric, according to Aristotle, are considered: the speaker’s qualifications, the dispositions of the auditorium and the uttered speech. The work presents biographical information about Katzenstein, positioning herself as a speaker authorized to utter discourses about psychological and educational themes. It also presents a characterization of the context in which the speaker pronounces the speech focusing particularly the movement of educational renewal named New School. Based on these data, it is made a characterization of the auditoriums to which the articles are destined; it is also made an exam of the articles according to dialectical and rhetorical concepts. Keywords: Brazilian Education - New School - Pedagogical Discourse - Rhetorical Analysis